Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1021/cs501153p
|View full text |Cite
|
Sign up to set email alerts
|

Ab Initio Study of Thin Oxide–Metal Overlayers as an Inverse Catalytic System for Dioxygen Reduction and Enhanced CO Tolerance

Abstract: Using first-principles density functional theory calculations, we used a thin oxide overlayer, such as MgO, on a metal surface as an inverse catalyst for dioxygen reduction. Surface distortions in the oxide layer, combined with the tunneling of electron from the underneath metal, activated the adsorbed O 2 in the form of a superoxo or peroxo. On the other hand, the thin MgO overlayer readily prevents the π-back-bonding between CO and the metal surface, thereby efficiently mitigating the affinity of the metal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 58 publications
(103 reference statements)
0
44
0
Order By: Relevance
“…However, its ORR catalytic activity can be signicantly improved by surfactant exfoliation, hetero-atom or metal doping, and deposition on metal supports. [18][19][20][21][22][23][24][25][26] Gao et al investigated the role of different defects for Cu supported BN and found that a boron vacancy helps in binding ORR intermediates more strongly. 27 On the other hand, h-BN exhibits other unique properties such as high stability which is favorable for the ORR.…”
Section: Introductionmentioning
confidence: 99%
“…However, its ORR catalytic activity can be signicantly improved by surfactant exfoliation, hetero-atom or metal doping, and deposition on metal supports. [18][19][20][21][22][23][24][25][26] Gao et al investigated the role of different defects for Cu supported BN and found that a boron vacancy helps in binding ORR intermediates more strongly. 27 On the other hand, h-BN exhibits other unique properties such as high stability which is favorable for the ORR.…”
Section: Introductionmentioning
confidence: 99%
“…The steps to estimate reaction free energies and adsorption free energies of intermediates are given in the Supporting Information . The Δ G OH is an efficient quantifying parameter of catalytic activity, as a plot of Δ G OH versus overpotential yields a volcano‐type relationship, from which the optimal binding strength of OH can be identified .…”
Section: Resultsmentioning
confidence: 99%
“…Quite recently, some works suggested that this electron tunneling concept could be active in the case of electrochemical reactions. DFT calculations performed on MgO(100) ultrathin films supported on Ag(100) suggested the existence of electron tunneling through the oxide toward some key intermediates involved in the oxygen reduction reaction (ORR), resulting in a system with activity comparable with Pt. The exploitation of electron tunneling in electrocatalysis seems to be quite general; for example other authors suggested that the adsorption energy of hydrogen, a key descriptor in the hydrogen evolution reaction, on the surface of monolayer MoS 2 is dictated by the value of the work function of the supporting metal …”
Section: The Metal/oxide Interfacementioning
confidence: 99%